Práctica de valores y las relaciones interpersonales en niños de la Institución Educativa Inicial N° 274 Caballococha 2023 - Salate Sinarahua, Rosa (2024)
The purpose of this research was to analyze the understanding between the implementation of values and interpersonal interactions in children enrolled in the Initial Educational Institution No. 274 Caballococha during the year 2023. The methodological approach adopted was characterized by its quantitative and relational nature. , with a non-experimental research design. The total population (N) included 87 children enrolled in said institution, and it was decided to use a sample size equivalent to the size of the population. Data collection was carried out through observation, using a specific guide as a recording instrument. The results obtained from Spearman's Rho compensation coefficient gave a value of 0.096. Consequently, the research hypothesis is rejected, confirming the alternative hypothesis that there is no significant relationship between the practice of values and interpersonal relationships in the children of the Initial Educational Institution N°274 Caballococha during the year 2023.